Dampak Badan Usaha Milik Desa (BUMDes) dalam Meningkatkan Kesejahteraan Masyarakat Desa Air Buluh Kecamatan Ipuh Kabupaten MukoMuko - Yayang Amelisa Pratiw; Faizal Anwar; Sri Indarti; Rekho Adriadi (Program Studi Administrasi Publik Universitas Muhamamdiyah Bengkulu, 2022)
The big goal of the State of Indonesia is the welfare of the community, to realize this it is important to have supporting facilities. One of the facilities that can support the realization of this is the existence of Village Owned Enterprises (BUMDes). BUMDes as a village economic strengthening that is engaged in social and economic fields and as a service provider to rural communities, especially regarding the business sector. This research is to see how the impact of BUMDes on the welfare of the community in Air Buluh Village, Ipuh District, Mukomuko Regency. The research method used in this descriptive qualitative research, primary and secondary data sources. The results of the study show that the more small and medium enterprises are growing, the average family member has a high school education, the village community gets adequate health services